Gods or Monsters? Non-Explicit Consent in the hastening of deaths by Intensivists in Belgium - Shanthi Van Zeebroeck (SciMedicine Journal, 2019)
The Belgian Euthanasia Act of 2002 (The Act), amended in 2014 to include the Minor Act (The Minor Act), has drawn international criticisms for its liberal laws and practices regarding Euthanasia. This research study is a response to media allegations that the liberal laws on euthanasia has encouraged doctors to adopt a paternalistic approach towards their patients by terminating their lives without their explicit consent, i.e. engaging in involuntary Euthanasia. Although in theory, only voluntary euthanasia (explicit patient request and therefore consent) is permitted in Belgium, the media allegations implied that in practice, involuntary euthanasia (no explicit patient request and therefore no consent) is practiced, especially in the Intensive Care Units (ICUs) in Belgium. One major criticism is that because of its liberal laws, Belgian doctors are killing patients without their non-explicit consent. Specifically, it is alleged that Intensivists are shortening lives or hastening the deaths of their patients without their non-explicit consent in the ICUs in the Wallonia Region in Belgium. This research study conducted an empirical-qualitative study to discover if these media allegations were true or false, by interviewing heads of ICUs in five major hospitals in the Wallonia region in Belgium. The research discovered that the media allegations are true, but they are also false. The media allegations are true because shortening life or hastening the death is sometimes practiced in the ICUs without the patient’s non-explicit consent. The media allegations are false because consent is not available due to the patient’s critical condition, and not because it was not asked for. In other words, what is practiced in the ICUs is non-voluntary euthanasia or where patient is unable to request or consent to euthanasia.